Glycyrrhizin as a potential disease-modifying therapy for epilepsy: insights into targeting pyroptosis to exert neuroprotective and anticonvulsant effects - Wei, Lei; Ou, Sijie; Meng, Youshi; Sun, Lanfeng; Zhang, Lin; Lu, Yuling; Wu, Yuan (Frontiers in Pharmacology, 2025)
BackgroundFor patients with epilepsy, antiseizure medication remains the primary treatment; however, it is ineffective in approximately 30% of cases. These patients experience progressive neuronal damage and poor outcomes. Therefore, there is an urgent need for disease-modifying therapy (DMT) that targets the pathogenesis of epilepsy. Glycyrrhizin has shown potential as a DMT in epilepsy due to its multiple targets and diverse mechanisms. Previous studies suggest that glycyrrhizin may regulate key processes involved in epilepsy pathogenesis, such as neuroinflammation and cell death, but its effects on pyroptosis have not been reported.MethodsThis study employed bioinformatics techniques to identify potential molecular targets for glycyrrhizin in epilepsy treatment and then validated using a kainic acid-induced status epilepticus mouse model.ResultsGlycyrrhizin treatment significantly prolonged seizure latency, reduced seizure duration, and alleviated neuronal damage in the status epilepticus mouse model. Molecular experiments indicated that glycyrrhizin may regulate pyroptosis through mediation of the high mobility group box 1 (HMGB1)/Toll-like receptor 4 (TLR4)/nuclear factor kappa-B (NF-κB) signaling pathway.ConclusionGlycyrrhizin exerts neuroprotective and anticonvulsant effects in epilepsy by regulating pyroptosis via the HMGB1/TLR4/NF-κB signaling pathway, offering novel insights into its potential as a DMT for epilepsy.